2013
DOI: 10.1158/0008-5472.can-13-0280
|View full text |Cite
|
Sign up to set email alerts
|

AC1MMYR2, an Inhibitor of Dicer-Mediated Biogenesis of Oncomir miR-21, Reverses Epithelial–Mesenchymal Transition and Suppresses Tumor Growth and Progression

Abstract: The extensive involvement of miRNAs in cancer pathobiology has opened avenues for drug development based on oncomir inhibition. Dicer is the core enzyme in miRNA processing that cleaves the terminal loop of precursor microRNAs (pre-miRNAs) to generate mature miRNA duplexes. Using the three-dimensional structure of the Dicer binding site on the pre-miR-21 oncomir, we conducted an in silico high-throughput screen for small molecules that block miR-21 maturation. By this method, we identified a specific small-mol… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
146
2
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(152 citation statements)
references
References 50 publications
3
146
2
1
Order By: Relevance
“…MicroRNAs are small (19-25 nucleotides) noncoding RNAs capable of modulating the expression of their cognate target genes by binding to the 3'-UTR of target mRNAs and causing either translational inhibition or mRNA cleavage (21). Aberrant miRNA expression contributes to the proliferation, invasion, or metastatic behavior of human cancers (22).…”
Section: Discussionmentioning
confidence: 99%
“…MicroRNAs are small (19-25 nucleotides) noncoding RNAs capable of modulating the expression of their cognate target genes by binding to the 3'-UTR of target mRNAs and causing either translational inhibition or mRNA cleavage (21). Aberrant miRNA expression contributes to the proliferation, invasion, or metastatic behavior of human cancers (22).…”
Section: Discussionmentioning
confidence: 99%
“…The results indicated that the level of miR-21 obtained via CHA-based assay were in consistent with the RT-PCR results of miR-21 expression between MCF-7 and MCF-10A cells. AC1MMYR2, an inhibitor of miR-21, which blocked the generate process of pre-miR-21 to mature miR-21 in glioblastoma, breast cancer, and gastric cancer cells (Ren et al, 2015;Shi et al, 2013). miR-21 expression was tested using CHA-based assay in MCF-7, MCF-10A, MDA-MB-231, HeLa and MDA-MB-435 by AC1MMYR2 (Figs.…”
Section: Real Sample Assaymentioning
confidence: 99%
“…Accumulating evidence indicates that abnormal miRNAs can function as oncogenes or tumor suppressors in the initiation and progression of human cancers, including GC [16,17,18]. For instance, miR-21 has been found to be overexpressed in GC and to promote tumor proliferation and invasion by negatively regulating important tumor suppressor genes such as PTEN, PDCD4, and RECK [19,20,21]. By contrast, overexpression of miR-141 could suppress GC cell invasion by directly repressing STAT4 [22].…”
Section: Introductionmentioning
confidence: 99%